2021
DOI: 10.3390/ijms22073356
|View full text |Cite
|
Sign up to set email alerts
|

Can Natural Products Exert Neuroprotection without Crossing the Blood–Brain Barrier?

Abstract: The scope of evidence on the neuroprotective impact of natural products has been greatly extended in recent years. However, a key question that remains to be answered is whether natural products act directly on targets located in the central nervous system (CNS), or whether they act indirectly through other mechanisms in the periphery. While molecules utilized for brain diseases are typically bestowed with a capacity to cross the blood–brain barrier, it has been recently uncovered that peripheral metabolism im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 235 publications
0
28
0
Order By: Relevance
“…Inflammation and neurodegeneration are often associated in neurological disorder [37]. Different studies suggest that polyphenols, alkaloids, terpenoids, steroids, and lignans can attenuate the inflamed and damaged BBB thus acting as curative agent against neurovegetative disorders [38,39] Previously, ferulic acid was physiologically detected in the cerebrospinal fluid (CSF) of mice and rat [40,41]. Interestingly, a recent study demonstrated the presence of non-endogenous caffeic acid in the human CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and neurodegeneration are often associated in neurological disorder [37]. Different studies suggest that polyphenols, alkaloids, terpenoids, steroids, and lignans can attenuate the inflamed and damaged BBB thus acting as curative agent against neurovegetative disorders [38,39] Previously, ferulic acid was physiologically detected in the cerebrospinal fluid (CSF) of mice and rat [40,41]. Interestingly, a recent study demonstrated the presence of non-endogenous caffeic acid in the human CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we used doses of drugs and food constituents up to 100 μM or 100 μg/mL because our main objective was to compare the response of intracellular and extracellular ACh. Given the metabolic process and existence of the blood–brain barrier, it is unlikely for some drugs and food constituents evaluated in this study to reach the brain at such doses [ 43 ]. The assay model described here should serve as a preliminary in vitro screen, and further in vivo and clinical studies are needed to clarify whether the candidates selected using this screening model could improve ACh transmission, neural plasticity, and even cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of the BBB severely prevents most drugs such as many polyphenols from entering the brain to exert their effects [386]. Although a large number of studies have shown that some plant polyphenols can cross the BBB and reach the brain to exert a neuroprotective effect, there are still many polyphenols reported having indirect beneficial effects in neurodegenerative diseases [387][388][389]. There is growing evidence of stronger two-way communication between the gut and the brain through the neural, endocrine, and immune systems, called the brain-gut axis [390].…”
Section: Indirect Beneficial Effect Of Plant Polyphenols On Neurodege...mentioning
confidence: 99%
“…Recent studies have shown a tight association between dysbiosis of the intestinal flora and several neurodegenerative diseases, such as AD and PD [391]. Therefore, targeting regulation of the intestinal microbiota is an important strategy for the treatment of neurodegenerative diseases [389]. For example, it has been found that curcumin plays a neuroprotective role by affecting intestinal microorganisms [392].…”
Section: Indirect Beneficial Effect Of Plant Polyphenols On Neurodege...mentioning
confidence: 99%